NM Symphony to fill Shuler with beautiful music - Donati, Bill (Raton, NM Raton Range, 1995)
Article about the New Mexico Symphony to play at the Shuler Theater.
Newspaper article + photograph of Jeffrey Anderson, Roger Melone, Byron Herrington, and Jean-Luc Matton.
Master list item #: 55
File location is in the Raton file Cabinet
Keywords: Anderson, Jeffery -- Musician/Tuba; Melone, Roger -- Conductor; Herrington, Byron -- Narrator; Matton, Jean-Luc -- Musician/Bass; New Mexico Symphony Orchestra -- Music Group; New Mexico Arts Division -- Donator; Santa Fe Pacific Foundation -- Donator; Art Promotion; Live Performance Promotion; Art and Humanities Council; Music Performance; Shuler Theater; Raton, New Mexico